Using Team-Pair-Solo to Improve Students’ Reading Comprehension toward The Eleventh Grade of 11S-4 SMAN 4 - Setyawati, Lely (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL; Vol 1 No 1 (2019): Education and Linguistics Knowledge Journal (Edulink)DO - 10.32503/edulink.v1i1.452, 2019)
This research aimed to apply Team Pair Solo technique to improve students’ reading problemof XI IIS-4 of SMAN 4 Kediri. This research design was a Classroom Action Research. The researcher used several instruments; such as observation checklist, field notes, and reading comprehension test. The finding showed that by using Team Pair Solo technique can improve students’ comprehension in than when they were taught by using previous method. The improvement of students’ reading comprehension was due to the use of Team Pair Solo as the technique in teaching reading.It showed that by using Team Pair Solo, students’ motivation and accommodate students to be well prepared to the reading passage by discussing in team, pair with other student, and finally they have great self-esteem to stand by their self in reading class. It was suggested to all English teachers to apply this technique as one of the methods to increase students’ motivation in English class and also could be used to increase students’ reading skill.